Impact of Branding on Consumer Behaviour at Himalayan Java Coffee Shops in Kathmandu Valley - Karanjit, Shriya; Agrawal, Payal; Tamang, Sanjita (Journal of Business and Social Sciences Research, 2024)
The study examines how branding affects consumer behaviour of consumers visiting Himalayan Java Coffee Shops in Kathmandu Valley by assessing the mediating effect of consumer attitude in relation to the branding elements (brand image, brand loyalty, brand trust and brand experience). The cross-sectional data was purposefully collected from 208 respondents ranging from under 18 years to older people residing in the Kathmandu Valley and previously who are exposed to consumption of coffee. Primary data was analysed quantitatively by using SMART-PLS. The study findings indicated significant impact of the constructs – Brand Image, Brand Loyalty, Brand Trust and Brand Experience on consumer behaviour at Himalayan Java. Additionally, the structural model affirmed that consumer attitude would act as a mediator in the relationship between Brand Image, Brand Loyalty, Brand Trust and Brand Experience. By filling in empirical gaps and utilising Theory of Planned Behaviour (TPB), this study advances our knowledge of how Brand Image, Brand Loyalty, Brand Trust and Brand Experience impacts consumer behaviour especially in case of Himalayan Java. The study stresses the eminent role of branding that impacts the consumer behaviour with the potential to assist the managers of several service and manufacturing industries to consider various branding elements when reaching out to the customers.